Tanggung Jawab Hukum Dinas Perhubungan dalam Pengawasan dan Regulasi Transportasi Online di Indonesia - Salsabila, Adinda Putri; Yasarman, Yasarman (Decisio: Jurnal Ilmiah Hukum, 2024)
The rapid development of online transportation in Indonesia has brought significant challenges in regulatory and supervisory aspects. The lack of clear legal frameworks has led to conflicts between conventional and online transportation operators, raising concerns about legal certainty and public safety. The Department of Transportation, as the main regulatory body, plays a crucial role in overseeing and enforcing policies related to online transportation services. However, inconsistencies in the implementation of regulations at the central and regional levels create further complexities in ensuring compliance. This study employs a qualitative method with a normative legal approach, focusing on regulatory analysis and the interpretation of legal norms in practice. Data collection is conducted through a comprehensive literature study, analyzing primary sources such as laws, regulations, and court decisions, as well as secondary sources including legal books, journals, and previous research.The findings indicate that despite existing regulations, the effectiveness of legal enforcement remains limited due to weak coordination between authorities and inadequate monitoring mechanisms. The study also reveals gaps in legal protection for online transportation drivers and users, highlighting the need for more structured policies and digital-based monitoring systems. Strengthening legal harmonization between central and regional regulations is essential to prevent regulatory conflicts and improve law enforcement. In conclusion, a more integrated and adaptive regulatory framework is needed to enhance the safety, fairness, and sustainability of online transportation in Indonesia